你可能感兴趣的试题
2x-y-3=0 x-2y+3=0 2x+y+5=0 x+2y-5=0
2x+y+5=0或2x+y﹣5=0 2x+y+
=0或2x+y﹣
=0 2x﹣y+5=0或2x﹣y﹣5=0 2x﹣y+
=0或2x﹣y﹣
=0
y=-2x-5 y=2x-5 y=2x+5 y=5-2x
y=-2x-5 y=2x-5 y=2x+5 x=
x+2y-5=0 x+2y+5=0 2x-y=0或x+2y-5=0 2x-y=0或x-2y+3=0
-3x2y·5x2y=2x2y -2x2y3·2x3y=-2x5y4 35x3y2÷5x2y=7xy (-2x-y)(2x+y)=4x2-y2
2x+y-12=0 2x+y-12=0或2x-5y=0 x-2y-1=0 x+2y-9=0或2x-5y=0
y=2x2+5 y=2x2﹣5 y=2(x+5)2 y=2(x﹣5)2
(x-5y+1)(x-5y-8) (x-5y+4)(x-5y-2) (x-5y-4)(x-5y-2) (x-5y-4)(x-5y+2)
(x-2)2+y2=5 x2+(y-2)2=5 (x+2)2+(y+2)2=5 x2+(y+2)2=5
x=3,y=2 x=2,y=3 x=0,y=5 x=5,y=0
x﹣2y﹣7=0 2x+y+1=0 2x﹣y﹣5=0 x+2y+5=0
3x2y﹣2x2y=x2y 5y﹣3y=2 ﹣3x+5x=﹣8x 3a+2b=5ab
2x<3y<5z 3y<2x<5z 5z<3y<2x 5z<2x<3y
2x+2y+x 2x+2y+y 2x+x+y 2x+y
(5x+y)2 5(x+y)2 5x+y2 (x+5y)2
y(x-y)+x(x-y)=(x-y)(x+y) 25x2-4y2=(5x+2y)(5x-2y) 4x2+20x+25=(2x+5)2 a2(a-b)-2a(a-b)+b2(a-b)=(a-b)3
x2+x2=x4 3x3y2﹣2x3y2=1 4x2y3+5x3y2=9x5y5 5x2y4﹣3x2y4=2x2y4
x+2; x-12y+2; -5x+12y+2; 2-5x.
y=6sin(5x+15)+2 y=6sin(5x-15)+2 y=6sin(5x+15)-2 y=6sin(5x-15)-2